Clika [videorecording (DVD)] - McBride, Sean (Screenwriter); Jones, Ski-ter; Humilde, Jimmy; Greene, Michael (C. Michael); Jay Dee (Singer); Doknow; Lopez, Laura; Ponceleon, Nana; Master P; Roberts, Eric, 1956-; Greene, Peter, 1965-2025; Chace, Alison (Sony Pictures Home Entertainment, 2026)
In the debut film from trailblazing music producer Jimmy Humilde's production company, aspiring small town musician Chito is determined to make it big. When a clip of him performing one of his songs goes viral, he seizes the opportunity and pushes to carve out a place for himself in the new wave of Mexican American music... and ultimately gets caught in a game more dangerous than anticipated. In a story of ambition, tradition, and self-discovery, Chito is ultimately forced to confront the choices he's made in his relentless pursuit of the American Dream.